Analisa dan Tinjauan Hukum atas Kebijakan Pengembangan dan Pemanfaatan Kendaraan Bermotor Listrik pada Sektor Pariwisata Indonesia - Mahardhika Berliandaldo; Ari Prasetio (Sanskara Hukum dan HAM, 2022)
The development of electric motor vehicles in Indonesia is a follow-up to Presidential Regulation No. 55/2019, which aims to maintain environmental sustainability, energy security, and be surprised at reducing the impact of CO2 emissions. In relation to the tourism sector, this step is an initiative in creating clean and environmentally friendly air quality, as well as maintaining natural and environmental conditions to remain sustainable. The legal analysis is shown to explain various regulatory derivatives that support the policy of developing electric motor vehicles and the policy of implementing the development of low-carbon transportation in the tourism sector. This research uses qualitative methods with a desk study approach and a statutory approach (statue approach). The results of the analysis obtained from the procurement policy for official and operational vehicle procurement for the government, the electric vehicle conversion policy, the incentive policy for ownership of electric vehicle loans, the subsidy policy for electric vehicle owners, the battery standardization policy, and the governance policy for used batteries, are a series of programs to accelerate the development of electric motor vehicles in Indonesia. In relation to the tourism sector, these policies can be in line with the concept of sustainable tourism as stated in various regulations and policies such as Law No. 17/2007, Law No. 10/2009, Government Regulation No. 50/2011, Regulation of the Minister of Tourism and Creative Economy No. 9/2021, and Presidential Instruction No. 7/2022 related to the use of electric motor vehicles in tourism destinations throughout Indonesia. The results of the research are expected to encourage an acceleration program for the use of electric motor vehicles in all tourism destinations, with the aim of realizing Indonesian tourism to meet sustainable principles in environmental, economic, and socio-cultural aspects.